Analisis Faktor yang Menyebabkan Penyimpangan Galvanometer dan Kondisi Lampu dengan Hukum Faraday Menggunakan Laboratorium Virtual PhET - Rahmawati, Amalia Darozatun; Malik, Adam (Jurnal Penelitian dan Pembelajaran Fisika Indonesia, 2024)
This study aims to explore the concept of Faraday's Law by allowing us to understand what factors can affect the deviation of the galvanometer needle and lamp conditions. The method used is experimental method using PhET virtual laboratory. This study shows that there are factors that affect the deviation of the galvanometer needle, namely the orientation of the poles on the magnet that is moved near or away from the coil. The factors that affect the condition of the lamp are the number of turns on the coil and the speed of the magnet movement when approaching or moving away from the coil. Keywords: EMF, Faraday's Law, PhET Virtual Laboratory.